Anti-Defection Laws in Ethiopia: Is There Any Constitutional Room? - Leake Mekonen Tesfay (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
Anti-defection laws are laws by which members of parliaments (MPs) who changed their party affiliation or voted against the position of their political faction or independent MPs who joined a political party are forced to vacate their parliamentary seat or prohibited from nomination as candidates of another political party in the next election. The essence of anti-defection laws is restricting political party members’ freedom to change their party affiliation to prevent government parties’ loss of majority in the parliament. Anti-defection laws are not uniformly used. While many established democracies see parliamentary defection as a manifestation of democracy, other jurisdictions with undeveloped democracies have outlawed defection. In Ethiopia, the FDRE Constitution entitles MPs to be led by the Constitution itself, peoples’ will, and their conscience, not necessarily by their party line. Accordingly, MPs can opine and vote contrary to the views of the political party of their membership in parliamentary debates; they can even change their party affiliation without risk of losing their parliamentary mandate. This makes Ethiopia one of the countries without anti-defection laws.